Monitoring Digital dalam Implementasi Program 7 Kebiasaan Anak Indonesia Hebat: Pengalaman Guru dan Peserta Didik - Hamdi Hamdi; Badarudin Badarudin; Abdul Rasyad (Universitas Hamzanwadi, 2025)
The implementation of the Seven Habits of Great Indonesian Children (7 KAIH) Program represents a national initiative to strengthen character education through the cultivation of positive daily habits among students. However, the effectiveness of the program depends not only on its policy design but also on its implementation process, participants' lived experiences, and the integration of digital technology as a monitoring mechanism. This study aimed to explore teachers' and students' lived experiences in implementing the digitally monitored 7 KAIH Program and to examine its perceived meaning for students' learning motivation and learning outcomes at SMKN 1 Batukliang Utara. A qualitative phenomenological approach was employed. Data were collected through in-depth interviews, observations, and document analysis involving the principal, teachers, homeroom teachers, and students participating in the program. Data trustworthiness was ensured through source, technique, and time triangulation, while data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing and verification. The findings indicate that digital monitoring functions not only as a reporting system but also as a medium for self-reflection, discipline reinforcement, accountability, and communication among schools, students, and parents. The program contributes to improved learning motivation by fostering more organized daily habits, although its effectiveness is constrained by limited digital infrastructure, inconsistent reporting practices, and varying levels of parental involvement. The study concludes that integrating character education with digital monitoring systems strengthens adaptive school culture and supports sustainable character development while enhancing students' motivation and learning outcomes.